Prediction of heat transfer in a circular tube with aluminum and Cr-Ni alloy pins using artificial neural network - Berber, Adnan; Gürdal, Mehmet; Bağırsakçı, Kazım (Informa UK Limited, 2020)
This work aims to estimate the experimental heat transfer coefficients of a circular channel using artificial neural network. The experiments are carried out at a forced turbulent flow regime of 10...